Network Infrastructure Practices in Large Australian Organisations - Dell, Peter; Issa, Tomayess; Ding, Ding (Curtin University of Technology, School of Economics and Finance, 2006)
Structured cabling is the network infrastructure embedded within a building?s structure. Installing appropriate cable types is important, as changes are costly and disruptive. This study investigates trends in structured cable infrastructure in Australia. Results suggest that many of the established reasons for adopting different transmission media are often not considered. The prevailing view is that there is no clear favourite backbone medium in Australia, which creates uncertainty for those organisations wishing to upgrade or install new infrastructure. Copper, however, is clearly the preferred medium for horizontal connections.